Differential regulation of endogenous and transduced beta-globin genes during infection of erythroid cells with a herpes simplex virus type 1 recombinant. - Smibert, C A (1990)
We infected murine erythroleukemia cells with a nondefective herpes simplex virus (HSV) type 1 recombinant bearing the rabbit beta-globin gene under the control of its own promoter, in order to compare the regulation of a cellular gene residing in the viral genome to that of its active endogenous counterpart. We found that the viral globin gene was activated by HSV immediate-early polypeptides, whereas expression of the endogenous beta-globin gene was strongly suppressed: transcription was greatly inhibited, and beta-globin mRNA was rapidly degraded. Degradation of globin mRNA was induced by a component of the infecting virion and required a functional UL41 gene product. These results demonstrate that HSV products can have opposing effects on the expression of homologous genes located in the cellular and viral genomes and suggest that the preferential expression of HSV genes that occurs during infection is not achieved solely through sequence-specific differentiation between viral and cellular promoters or mRNAs.